2012
DOI: 10.1177/1933719111418125
|View full text |Cite
|
Sign up to set email alerts
|

Premenopausal Women Exhibit an Inherent Protection of Endothelial Function Following a High-Fat Meal

Abstract: Endogenous estrogens likely increase blood flow and subsequently shear stress but have also been associated with improved endothelial function and cardiovascular protection. In contrast, a high-fat meal is thought to reduce endothelial function and increase cardiovascular risk. Therefore, we tested the hypotheses that fluctuating hormones across the menstrual cycle (1) facilitate an increase in shear rate and explain phase-specific differences in flow-mediated dilation (FMD) and (2) provide vascular protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(78 citation statements)
references
References 27 publications
10
62
6
Order By: Relevance
“…However, recent data from humans has suggested that a sexspecific effect of the exercise pressor reflex persists across the menstrual cycle, where endogenous hormones (estrogen and progesterone) oscillate from low to high concentrations, casting doubt on the estrogen dependence of this phenomenon (28). Furthermore, in agreement with the results of Jarvis et al (28), the present findings may also not depend on estrogen per se, as these experiments were performed in the early follicular phase of the menstrual cycle, where estrogen is at low levels, similar to that of men (15,21,56). Schmitt et al (53) indicated that, while the exercise pressor reflex can be suppressed by estrogen, there appears to be cross-talk between the estrogen and opioid systems, suggesting an indirect effect of estrogen.…”
Section: Sex Specificity In Central Hemodynamicssupporting
confidence: 92%
See 1 more Smart Citation
“…However, recent data from humans has suggested that a sexspecific effect of the exercise pressor reflex persists across the menstrual cycle, where endogenous hormones (estrogen and progesterone) oscillate from low to high concentrations, casting doubt on the estrogen dependence of this phenomenon (28). Furthermore, in agreement with the results of Jarvis et al (28), the present findings may also not depend on estrogen per se, as these experiments were performed in the early follicular phase of the menstrual cycle, where estrogen is at low levels, similar to that of men (15,21,56). Schmitt et al (53) indicated that, while the exercise pressor reflex can be suppressed by estrogen, there appears to be cross-talk between the estrogen and opioid systems, suggesting an indirect effect of estrogen.…”
Section: Sex Specificity In Central Hemodynamicssupporting
confidence: 92%
“…They also had not performed any exercise within the past 24 h. Female subjects were eumenorrheic, not using chemical contraceptives, and were studied during days 1-7 of their menstrual cycle to reduce the impact of the cyclical nature of endogenous female hormones. Menstrual history was determined by questionnaire, and the current menstrual phase was identified by tracking the menstrual cycle for 1 mo before appropriately scheduling the study the following month, referred to as the forward counting method (21,26). The early follicular phase was chosen, as, previously, plasma estradiol, the primary biologically active estrogen, has been documented to not differ significantly between men and women during this phase (15,21,56).…”
Section: Subjects and General Proceduresmentioning
confidence: 99%
“…Our findings are further supported by the few studies that have examined FMD throughout the menstrual cycle where there are fluctuations in endogenous oestrogen production. Our group and others have reported a higher FMD in women during the late follicular (ovulation) and luteal phases compared with the early follicular phase (menses) . Though basal FMD fluctuates during the menstrual cycle, we and others have also reported a similar post‐prandial FMD that is not impacted by the menstrual cycle phase .…”
Section: Discussionsupporting
confidence: 65%
“…Raitakari et al [18] found a direct relationship between forearm blood flow and the rise in insulin levels following and reported a significant increase in baseline diameter using FMD, though the apparent reduction in FMD% itself did not reach statistical significance. A similar change in baseline arterial diameter has been reported by Harris et al [35] following a high-fat meal. In addition, the inhibition of eNOS has been found to increase aortic compliance, as measured by PWV [36].…”
Section: Discussionsupporting
confidence: 68%